2009
DOI: 10.1111/j.1365-2591.2008.01514.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of ethylenediaminetetraacetic, etidronic and peracetic acid irrigation on human root dentine and the smear layer

Abstract: The decalcifying agents under investigation were all able to remove or prevent a smear layer. However, they eroded the dentine wall differently.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

10
288
1
22

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 238 publications
(333 citation statements)
references
References 27 publications
(46 reference statements)
10
288
1
22
Order By: Relevance
“…24 PAA solution contains and liberates acetic acid, which is a weak chelating agent, but can reduce the smear layer as effective as EDTA. 23 The results of this study necessitates rejection of the null hypothesis, because the debonding values obtained after PAA treatment were statistically similar to those of EDTA-treated specimens.…”
Section: Discussionmentioning
confidence: 81%
See 2 more Smart Citations
“…24 PAA solution contains and liberates acetic acid, which is a weak chelating agent, but can reduce the smear layer as effective as EDTA. 23 The results of this study necessitates rejection of the null hypothesis, because the debonding values obtained after PAA treatment were statistically similar to those of EDTA-treated specimens.…”
Section: Discussionmentioning
confidence: 81%
“…22 Hence, the use of alternative chelating solutions with less or no detrimental effect on root dentin would be most desirable. 23 Among several decalcifying agents available, PAA appears to be a potential alternative to EDTA to dissolve the smear layer and disinfect the root canal system. 23,24 A previous study has shown that 1% PAA had similar effect against Enterococcus faecalis compared with NaOCl and chlorhexidine.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An antimicrobial effect and a modification or dissolution of the smear layer is desired. The application of chlorhexidine or sodium hypochlorite to prepared dentin surfaces has been suggested for this purpose [10]; however previous results have shown that these solutions are not capable of completely removing the smear layer present after cavity preparation [11,12]. Furthermore, these solutions may be less than ideal in combination with adhesive techniques because of their hampering effect on bond strength [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, these solutions may be less than ideal in combination with adhesive techniques because of their hampering effect on bond strength [13][14][15]. To ensure bacterial elimination in dentinal tubules, the smear layer must be removed by a strong chelator or an acid [11]. Treating dentin and enamel with acid or acid-containing liquids is widely used for routine bonding procedures.…”
Section: Introductionmentioning
confidence: 99%